Pilates method in diabetes control in pregnant women: a systematic review (Research, Society and Development, 2022)
Pregnancy is a period of many changes in a woman's body designed to promote the growth of the fetus. Gestational diabetes mellitus (GDM) is defined as carbohydrate intolerance that occurs for the first time during pregnancy. Physical exercise has minimal benefits and risks for pregnant women, and is important for the health of women with gestational diabetes mellitus. The Pilates method is a system of exercises based on the philosophy and principles of the body, mind and spirit. This study aimed to show if the practice of Pilates is really effective when compared to the effects of standard physical exercise during pregnancy in women with diabetes, so that this practice will contribute to the control of blood glucose levels. Searches were carried out in the following databases: PEDro (Physiotherapy Evidence Database), PubMed (National Library of Medicine) and VHL (Virtual Health Library). In the results, only 04 randomized clinical trials out of 116 were relevant and that met the eligibility criteria according to the methodological quality assessment of the PEDro Scale. In the discursive analysis, the articles exposed in this study were analyzed according to the gestational age of the participants, standard physical exercise interventions regarding the reduction of diabetes mellitus in pregnant women. However, there were no statistically significant differences between the intervention groups, so the evidence was insufficient to suggest that physical exercise during pregnancy can be effective in reducing the risk of gestational diabetes mellitus and in reducing blood glucose levels.